Environmental Economics for Environmental Protection - Ekko van Ierland; Corjan Brink; Leen Hordijk; Carolien Kroeze (The Scientific World Journal)
Environmental economics deals with the optimal allocation of production factors and correcting market failure in protecting the environment. Market failure occurs because of externalities, common property resources, and public goods. Environmental policy instruments include direct regulation, taxes/subsidies, tradable permits, deposit systems, voluntary agreements, and persuasion.